Cross-serotype protection against group A Streptococcal infections induced by immunization with SPy_2191 - Pooja Sanduja (Nature Portfolio, 2020)
A high number of serotypes makes vaccine development to group A Streptococcus (GAS) difficult. Here, the authors use a reverse vaccinology approach and identify SPy_2191 as conserved surface protein that inhibits GAS adhesion and invasion and induces cross-protective immunity in mice.